Makānat Ṣaḥīḥ al-Bukhārī fī al-Maghrib al-Islāmī: Nuskhat Abī ʿAlī al-Ṣadafī Anmūdzajan - Ibn Housayn Tizaoui, Kamel (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study aims to highlight the extent to which Islamic scholars have shown deep interest in the second most important book for the entire Muslim ummah. Ṣaḥīḥ al-Bukhārī is ranked immediately after the Holy Qur’an, which explains its exceptional significance in al-Andalus and throughout the Islamic Maghrib. One distinguished scholar from this western region of the Islamic world—renowned for his brilliance and scholarly precision—received an authentic oral transmission of Ṣaḥīḥ al-Bukhārī. He subsequently produced, in his own handwriting, a uniquely valuable manuscript enriched with insightful marginalia and annotations that reflect his profound mastery of the text. This authentic recension of Ṣaḥīḥ al-Bukhārī, preserved by Abū ʿAlī al-Ṣadafī, forms a part of his larger encyclopedic manuscript. The manuscript of Abū ʿAlī al-Ṣadafī is of paramount importance because it reinforces the authenticity and unquestionable provenance of Ṣaḥīḥ al-Bukhārī. Islamic scholars have examined and authenticated this manuscript through methodologies rooted in the science of ḥadīth transmission, including oral verification, precise documentation, and comparative analysis. Therefore, the study of Abū ʿAlī’s manuscript provides significant evidence supporting the integrity and authenticity of Ṣaḥīḥ al-Bukhārī.